Homeopathy in healthcare -- effectiveness, appropriateness, safety, costs an HTA report on homeopathy as part of the Swiss Complementary Medicine Evaluation Programme - Bornhöft, Gudrun; Matthiessen, Peter F. (Springer, 2011)
This volume includes the full Health Technology Assessment (HTA) report on effectiveness, appropriateness, safety and costs of homoeopathy in health care. The report was commissioned by the Swiss health authorities to inform decision-making on the further inclusion of homoeopathy in the list of services covered by statutory health insurance. Other studies carried out as part of the Swiss Complementary Medicine Evaluation Programme (PEK) caused a massive stir due to their schematic and exclusively quantitative (negative-)outcomes for homoeopathy. The present report, in contrast, offers a differentiated evaluation of the practice of homoeopathy in health care. It confirms homoeopathy as a valuable addition to the conventional medical landscape ? a status it has been holding for a long time in practical health care.